Desa Canggu, Bali Sebuah Basecamp Bagi Digital Nomad? Identifikasi Produk Wisata Berdasarkan 4 A (Attraction, Amenity, Accessibility, Ancilliary) - Prabawati, Ni Putu Diah (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
The village of Canggu, Bali is very well known among digital nomadic tourists. The purpose of this study is to identify tourism products in terms of 4A to support the needs of digital nomadic tourists in traveling and how are the perceptions of digital nomadic tourists towards Canggu Village, Bali. The data analysis technique used in this research is descriptive qualitative analysis. Identification of tourism products based on 4A, namely attractions, amenities, accessibility, and additional services. Nomad digital tourists make Canggu Village a base camp because all the supporting components for digital tourism activities are available. The existence of communities such as digital camps and nomad academies forms an ecosystem for nomadic tourists. As for things that should be addressed, namely traffic factors, security.